Labeled silica-coated gold nanorods and method for producing same
Silica-coated gold nanorods with chemically bonded spacers address shape stability and fluorescence intensity issues, offering stable and sensitive luminescent agents for bioimaging and nanotherapeutics.
Patent Information
- Application Number
- JP2020209844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-09
- Filing Date
- 2020-12-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Existing gold nanorods face issues with shape stability and fluorescence intensity variations due to flexible organic spacers and lack of chemical bonding, leading to reduced sensitivity and stability in biological environments.
Silica-coated gold nanorods with a spacer bonded through a silane coupling agent, ensuring a minimum thickness of 15 nm to maintain fluorescence intensity and stability, using a spacer derived from silane coupling agents with both inorganic and organic functional groups for chemical bonding.
The solution provides stable and highly sensitive luminescent agents that maintain fluorescence intensity, suitable for bioimaging and nanotherapeutic applications, with improved shape stability and safety for biological use.
Smart Images

Figure 0007607312000010 
Figure 0007607312000011 
Figure 0007607312000012
Abstract
Description
[Technical field]
[0001] The present invention relates to gold nanoparticles, and in particular to silica-coated gold nanorods having a labeling substance bound thereto. [Background technology]
[0002] Gold nanoparticles have attracted attention for their unique optical properties in the visible light region, and are therefore being used as nanomaterials for bioimaging, contrast agents, labeling agents, biosensors, and even as photothermal nanothermal drugs. In fact, gold nanoparticles are used as a coloring agent in pregnancy test kits that are commercially available and in simple influenza diagnostic kits used in hospitals.
[0003] Among these gold nanoparticles, gold nanorods, which are rod-shaped gold nanoparticles, have wavelengths of light absorption and scattering that can be extended to the near-infrared region (600-900 nm) known as the "biological window" of biological tissue transparency, making them useful for application in bioscience. However, there are concerns about the shape stability of gold nanorods in the nano-size region, and quenching phenomena due to light energy transfer near interfaces make it difficult to use them as highly sensitive luminescent agents.
[0004] Regarding luminescence, which is important for high-sensitivity bioimaging, it has been demonstrated that the fluorescence intensity varies depending on the distance between the core metal and the fluorescent site and the spacer length. In other words, the fluorescence intensity decreases as the spacer length decreases. For this reason, polymers, DNA, etc. have been used as spacers to adjust the luminescence (Non-Patent Document 1).
[0005] In addition, in cancer examinations, a contrast agent in which (ICG) is supported on a porous silica layer coated on gold nanorods is used to obtain X-ray CT and NIR fluorescent imaging images (Non-Patent Document 2).
[0006] Furthermore, Patent Document 1 discloses an invention of core-shell type gold nanoparticles that contain a phosphor and further utilize the "surface plasmon effect" to enhance the fluorescence generated by the phosphor in a display device that performs color display or a light source that emits colored light. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Appl. Phys. Lett., 2009, 94, 063111; J. Am. Chem. Soc., 2006, 128,5462-5467. [Non-Patent Document 2] Optics Express, 2011 Vol.19, No.18, 17030-17039 [Patent Document 1] Patent Publication No. 2016-216547 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the spacer in Non-Patent Document 1 is an organic substance, and has the problem of being flexible and lacking in stability.
[0009] Therefore, the inventors tried to silica-coat gold nanorods using a silane coupling agent as a spacer. However, as shown in the comparative experiment described below, the absorption spectrum showed a clear decrease in the absorption band due to the inability to disperse the sample, and the FE-SEM image revealed that silica coating was not achieved.
[0010] Next, the inventors attempted to silica-coat and fluorescently label gold nanorods using a mixture of tetraethoxysilane and a silane coupling agent. However, it became clear that the fluorescent intensity of the fluorescently labeled silica-coated gold nanorods produced by this method was reduced.
[0011] In addition, the contrast agent composed of gold nanorods disclosed in Non-Patent Document 2 has a problem in that the fluorescent substance is not chemically bonded but is only physically captured, and therefore lacks stability against temperature rise and the external environment. In addition, the fluorescent agent disclosed in Patent Document 1 utilizes the surface plasmon effect, and therefore the distance between the metal nanostructure and the fluorescent agent is short and must be strictly maintained, making it difficult to manufacture, and furthermore, there is a problem in that no consideration is given to safety when administered to a living body.
[0012] The inventors therefore demonstrated that by introducing a silane coupling agent into the silica layer of gold nanorods that have been silica-coated with tetraalkoxysilane and binding a fluorescent substance to the silane coupling agent, it is possible to produce fluorescently labeled silica-coated gold nanorods whose fluorescence intensity does not decrease, and thus completed the present invention.
[0013] An object of the present invention is to provide fluorescently labeled, silica-coated gold nanorods that are safe when administered to a living body, stable against temperature increases and the external environment, and easy to produce. [Means for solving the problem]
[0014] The present invention provides a labeled silica-coated gold nanorod comprising a gold nanorod, a silica layer covering the gold nanorod, a spacer bonded to the silica layer, and a labeling substance bonded to the spacer by a chemical bond.
[0015] This makes it possible to provide labeled silica-coated gold nanorods in which the fluorescence intensity of the fluorescent substance is not reduced to a level that does not impede practical use.
[0016] The thickness of the silica layer may be 15 nm or more, which keeps the labeling substance and the gold nanorods apart from each other, preventing a decrease in fluorescence intensity.
[0017] The spacer may be derived from a silane coupling agent comprising a Si atom and four functional groups directly or indirectly connected to the Si atom, the four functional groups comprising at least one inorganic functional group and at least one organic functional group.
[0018] The organic functional group may be at least one selected from the group consisting of a vinyl group, an epoxy group, a styryl group, a methacryl group, an acryl group, an amino group, a ureido group, an isocyanate group, an isocyanurate group, and a mercapto group.
[0019] The organic functional group may be indirectly connected to the Si atom via an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a phenyl group, a heterocyclic group, or a fused ring group.
[0020] The spacer may be vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, P-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, or 3-acryloxypropyltrimethoxysilane. , N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltrialkoxysilane, 3-isocyanatopropyltriethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, or 3-mercaptopropyltrimethoxysilane.
[0021] The present invention also provides a method for producing labeled silica-coated gold nanorods, comprising an introduction step of introducing a spacer into the silica layer of a silica-coated gold nanorod, and a binding step of binding a labeling substance to the spacer.
[0022] This makes it possible to produce labeled silica-coated gold nanorods in which the fluorescence intensity of the fluorescent substance is not reduced to a level that does not impede practical use.
[0023] The thickness of the silica layer may be 15 nm or more, which keeps the labeling substance and the gold nanorods apart from each other, preventing a decrease in fluorescence intensity. [Brief description of the drawings]
[0024] [Figure 1] Figure 1 shows the synthesis scheme of hexadecyltrimethylammonium bromide (CTAB) protected AuNR using the seed-mediated method. [Diagram 2] Figure 2 shows the absorption spectrum of AuNR. [Diagram 3] Figure 3 shows a field emission scanning electron microscope (FE-SEM) image of AuNR. [Figure 4] Figure 4 shows the particle size distribution of AuNR calculated from FE-SEM photographs. [Diagram 5] Figure 5 shows the fabrication scheme of silica-coated AuNR (AuNR@TEOS) using tetraethoxysilane (TEOS). [Figure 6] FIG. 6 shows the absorption spectra of AuNR and AuNR@TEOS. [Figure 7] FIG. 7 shows the Zeta potential of AuNR and AuNR@TEOS. [Figure 8] FIG. 8 shows the Fourier transform infrared (FT-IR) spectra of AuNR and AuNR@TEOS. [Figure 9]Figure 9 shows the FE-SEM image of AuNR@TEOS. [Figure 10] Figure 10 shows the silica layer distribution of AuNR@TEOS calculated from the FE-SEM photographs. [Figure 11] FIG. 11 shows the absorption spectra of AuNR, AuNR@TEOS, and AuNR@APTES. [Figure 12] Figure 12 shows the FE-SEM image of AuNR@APTES. [Figure 13] FIG. 13 shows a preparation scheme of AuNR@TEOS (AuNR@TEOS-APTES) into which APTES (-NH2 group) is introduced using 3-aminopropyltriethoxysilane (APTES). [Figure 14] FIG. 14 shows the absorption spectra of AuNR, AuNR@TEOS, and AuNR@TEOS-APTES. [Figure 15] FIG. 15 shows the Zeta potential of AuNR, AuNR@TEOS, and AuNR@TEOS-APTES. [Figure 16] FIG. 16 shows the FT-IR spectra of AuNR, AuNR@TEOS, and AuNR@TEOS-APTES. [Figure 17] Figure 17 shows the FE-SEM image of AuNR@TEOS-APTES. [Figure 18] Figure 18 shows the silica layer distribution of AuNR@TEOS-APTES calculated from the FE-SEM photographs. [Figure 19] FIG. 19 shows a preparation scheme of AuNR@TEOS-APTES modified with a Dansyl group (AuNR@TEOS-APTES-Dansyl) using Dansyl Chloride. [Figure 20] FIG. 20 shows the absorption spectra of AuNR@TEOS-APTES, AuNR@TEOS-APTES-Dansyl, and dansylated hexylamine. [Figure 21] FIG. 21 is an enlarged graph of the graph in FIG. [Figure 22] FIG. 22 shows a spectrum showing the difference in absorption spectrum between AuNR@TEOS-APTES and AuNR@TEOS-APTES-Dansyl (i.e., the difference before and after modification with Dansyl groups). [Figure 23] FIG. 23 shows the FT-IR spectra of AuNR, AuNR@TEOS, AuNR@TEOS-APTES, and AuNR@TEOS-APTES-Dansyl. [Figure 24] FIG. 24 shows the Zeta potential of AuNR, AuNR@TEOS, AuNR@TEOS-APTES, and AuNR@TEOS-APTES-Dansyl. [Diagram 25] FIG. 25 shows the FE-SEM image of AuNR@TEOS-APTES-Dansyl. [Figure 26] Figure 26 shows the silica layer distribution of AuNR@TEOS-APTES-Dansyl calculated from the FE-SEM photograph. [Figure 27] FIG. 27 shows the fluorescence spectra of AuNR, AuNR@TEOS, AuNR@TEOS-APTES, and AuNR@TEOS-APTES-Dansyl. [Figure 28] Figure 28 shows photographs of AuNR, AuNR@TEOS, AuNR@TEOS-APTES, and AuNR@TEOS-APTES-Dansyl placed in vials irradiated with UV (365 nm). [Figure 29] FIG. 29 shows the first fluorescence spectra of AuNR@TEOS-APTES-Dansyl and the standard substance, Quinine Sulfate Dihydrate. [Diagram 30] FIG. 30 shows the second fluorescence spectra of AuNR@TEOS-APTES-Dansyl and the standard quinine sulfate dihydrate. [Diagram 31]FIG. 31 shows the third fluorescence spectrum of AuNR@TEOS-APTES-Dansyl and the standard quinine sulfate dihydrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] <Definition> For convenience, certain terms used in this application are collected here. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise.
[0026] The numerical ranges and parameters given in the present invention are approximate values, but the numerical values given in the specific examples are described as precisely as possible. However, any numerical value inherently contains a certain error that necessarily results from the standard deviation found in each test measurement. Also, the term "about" as used herein generally means within 10%, 5%, 1% or 0.5% of a given value or range. Alternatively, the term "about" means within an acceptable standard error as considered by those skilled in the art.
[0027] Hereinafter, an embodiment of the present invention will be described. The following embodiment is merely an example, and the scope of the present invention is not limited to the following embodiment. Note that, in order to avoid repetition and complexity, explanations of similar contents will be omitted.
[0028] <Embodiment 1> The labeled silica-coated gold nanorods according to this embodiment comprise a gold nanorod, a silica layer covering the gold nanorod, a spacer bonded to the silica layer, and a labeling substance chemically bonded to the spacer.
[0029] The labeled silica-coated gold nanorod according to this embodiment includes a gold nanorod. The purity of the gold nanorod used in this embodiment is 75, 80, 85, 90, 95, 98, 99, 99.9, 99.99% or more, and may be within a range between any two of the numerical values exemplified here. The long axis of the gold nanorod used in this embodiment is 3, 10, 18, 32, 100, 180, 280, 400, 540, 800 nm, and may be within a range between any two of the numerical values exemplified here. The short axis of the gold nanorod used in this embodiment is 2, 5, 6, 8, 20, 30, 40, 50, 60, 80 nm, and may be within a range between any two of the numerical values exemplified here. The aspect ratio (long axis / short axis) of the gold nanorod used in this embodiment is 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, and may be within a range between any two of the numerical values exemplified here. The long and short axes of the gold nanorods can be measured from photographs taken with a scanning electron microscope.
[0030] In this embodiment, the average particle size of the gold nanorods is 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 nm, and may be within a range between any two of the numerical values exemplified here. The average particle size of the gold nanorods refers to the particle size at 50% of the integrated value in the particle size distribution obtained by measuring the diameter of the circle equivalent to the projected area of 200 particles randomly selected using a photograph taken by a scanning electron microscope. The average particle size of the gold nanorods may be calculated using a dynamic light scattering particle size distribution analyzer (DLS).
[0031] In this embodiment, the silica-coated gold nanorod is a gold nanorod covered with a silica layer. The thickness of the silica layer is 15, 20, 25, 30, 35, 40, or 45 nm, and may be within a range between any two of the numerical values exemplified here. The thickness of the silica layer can be measured from a photograph taken by a scanning electron microscope. The coverage of the gold nanorod with the silica layer is 60, 70, 80, 90, 95, 98, 99, 99.9, or 99.99% or more, and may be within a range between any two of the numerical values exemplified here. The coverage of the silica layer can be calculated from the length of the gold nanorod that is coated with silica around the entire circumference of the gold nanorod measured from a photograph taken by a scanning electron microscope. The gold nanorod is covered with a silica layer to stabilize the shape in the nano-sized region. The silica layer covering the gold nanorods can be produced by coating the surface of the gold nanorods with silica using an alkoxysilane (e.g., methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, dimethoxydiphenylsilane, n-propyltrimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltriethoxysilane, hexyltriethoxysilane, octyltriethoxysilane).
[0032] In this embodiment, a spacer is bonded to the silica layer. The spacer is derived from a silane coupling agent, and the silane coupling agent has a Si atom and four functional groups directly or indirectly connected to the Si atom, and the four functional groups have at least one inorganic functional group and at least one organic functional group. In this embodiment, the molar ratio of the silica-coated gold nanorods to the spacer introduced into the silica-coated gold nanorods is 1:2 to 20 (2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, and may be within a range between any two of the numerical values exemplified here).
[0033] The organic functional group may be at least one selected from the group consisting of a vinyl group, an epoxy group, a styryl group, a methacryl group, an acryl group, an amino group, a ureido group, an isocyanate group, an isocyanurate group, and a mercapto group, but is not limited thereto. The organic functional group may be indirectly connected to the Si atom via an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a phenyl group, a heterocyclic group, or a condensed ring group.
[0034] The inorganic functional group is a group in which silanol generated by hydrolysis forms a hydrogen bond with a hydroxyl group of an inorganic material (such as glass or silica), and is preferably an alkoxy group, more preferably a methoxy group or an ethoxy group. The inorganic functional group may be indirectly connected to the Si atom via an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a phenyl group, a heterocyclic group, or a fused ring group.
[0035] In this embodiment, the four functional groups may include an alkyl group having 1 to 3 carbon atoms (a methyl group, an ethyl group, a propyl group, or an isopropyl group) in addition to the inorganic functional group and the organic functional group. For example, the four functional groups may include three inorganic functional groups and one organic functional group, two inorganic functional groups and two organic functional groups, or two inorganic functional groups, one organic functional group, and one alkyl group having 1 to 3 carbon atoms.
[0036] The spacer may be vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, P-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, or 3-acryloxypropyltrimethoxysilane. , N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltrialkoxysilane, 3-isocyanatopropyltriethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, or 3-mercaptopropyltrimethoxysilane.
[0037] In this embodiment, the labeling substance (fluorescent substance, luminescent substance, radioactive substance, etc.) is bonded to the spacer by chemical bonding, so that the bond is strong and stable. Therefore, the bond will not be released even by an increase in temperature or the external environment. The labeling substance can be an enzyme such as peroxidase or alkaline phosphatase, 125 I, 131 I, 35 S, 3Examples of the labeling substance include, but are not limited to, radioactive substances such as H, fluorescein, rhodamine, dansyl, pyrene, anthraniloyl, nitrobenzoxadiazole, cyanine dyes (Cy3, Cy5, etc.), phycoerythrin, tetramethylrhodamine, fluorescent proteins (green fluorescent protein derived from Aequorea victoria, fluorescent protein derived from reef-building coral, fruit fluorescent protein, etc.), fluorescent substances such as near-infrared fluorescent materials, luminescent substances such as luciferase, luciferin, aequorin, and nanoparticles such as quantum dots. The labeling substance may be a biotin-avidin (or streptavidin) complex containing avidin or streptavidin labeled with the labeling substance, and a succinimidyl ester compound in which the labeling substance is bound to succinimide. The labeling substance of this embodiment and the organic functional group to which the labeling substance is bound can be appropriately changed depending on the intended use of the labeled silica-coated gold nanorod. In this embodiment, the molar ratio of the silica-coated gold nanorods into which a spacer has been introduced to the labeling substance introduced into the spacer is 1:2 to 20 (2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or may be within a range between any two of the numerical values exemplified here) when there is one organic functional group per spacer, and is 1:2 to 40 (2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, or may be within a range between any two of the numerical values exemplified here) when there is two organic functional groups per spacer.
[0038] In this embodiment, the gold nanorod is covered with a silica layer having a thickness of at least 15 nm, and the labeling substance is chemically bonded to the silica layer via a spacer, so that the gold nanorod and the labeling substance are separated by a distance of at least 15 nm. Therefore, quenching due to light energy transfer near the interface does not occur, and a stable and highly sensitive luminescent agent can be realized.
[0039] <Embodiment 2> The method for producing labeled silica-coated gold nanorods according to this embodiment includes an introduction step of introducing a spacer into the silica layer of the silica-coated gold nanorod, and a binding step of binding a labeling substance to the spacer.
[0040] In this embodiment, the introduction step can change the introduction conditions depending on the type of spacer to be introduced. The introduction conditions can be determined by using a known method. For example, 3-aminopropyltriethoxysilane (3-Aminopropyltriethoxysilane, When APTES is used, the introduction step includes a first mixing step of mixing the MeOH solution in which the silica-coated gold nanorods are dispersed with a NaOH solution while stirring, and a second mixing step of mixing the mixed solution obtained by the first mixing step with a MeOH solution in which APTES is dissolved while stirring, and the concentration ratio of the silica-coated gold nanorods to NaOH in the first mixing step is 1:0.8-1.5 (0.8, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, and may be within a range between any two of the numerical values exemplified here). The concentration ratio of the silica-coated gold nanorods to APTES in the second mixing step is 1:3-6 (3, 3.5, 4, 4.5, 5, 5.5, 6, and may be within a range between any two of the numerical values exemplified here). The above-mentioned introduction step may include a heating and stirring step in which, after the second mixing step, the mixed solution is stirred under a temperature condition of 40°C to 60°C for 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 hours, and the time is within a range between any two of the numerical values exemplified here.
[0041] In the first mixing step, the NaOH solution may be added to the MeOH solution in which the silica-coated gold nanorods are dispersed, in 2 to 4 portions every 20 to 40 minutes. In the first mixing step, the MeOH solution in which the silica-coated gold nanorods are dispersed may be a 20, 22, 24, 26, 28, or 30% MeOH solution, and may be within a range between any two of the values exemplified here. The stirring time in the second mixing step may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 minutes, and may be within a range between any two of the values exemplified here.
[0042] In this embodiment, the bonding step can change the bonding conditions according to the type of labeling substance to be chemically bonded and the type of organic functional group of the spacer. A known method can be used as the chemical bonding condition. For example, when a spacer having an amino group as an organic functional group and dansyl (dansyl group) as a labeling substance are used, the bonding step includes a third mixing step of mixing a dry CH2Cl2 solution in which silica-coated gold nanorods to which spacers have been introduced are dispersed with triethylamine under a nitrogen atmosphere while stirring, and a heating and refluxing step of mixing the mixed solution obtained by the third mixing step with a dry CH2Cl2 solution in which dansyl chloride has been dissolved, and heating and refluxing for 4, 5, 6, 7, 8, 9, 10, 11, or 12 hours, which is within the range between any two of the numerical values exemplified here. The heating and refluxing is performed under a temperature condition of 35°C to 45°C. The concentration ratio of the spacer-introduced silica-coated gold nanorods to triethylamine in the third mixing step is 1:0.8-5 (0.8, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 2.0, 3.0, 4.0, 5.0, or any two values between the values exemplified here). The concentration ratio of the spacer-introduced silica-coated gold nanorods to dansyl chloride in the heating and refluxing step is 1:20-40 (20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, or any two values between the values exemplified here).
[0043] The method for producing labeled silica-coated gold nanorods in accordance with this embodiment may include a coating step of coating the gold nanorods with silica, or may include a manufacturing step of producing gold nanorods and a coating step of coating the gold nanorods with silica.
[0044] Manufacturing steps to produce gold nanorods The steps for producing gold nanorods include, for example, a seed solution preparation step and a primary growth solution preparation step. The method includes a step of preparing a first growth solution and a step of preparing a second growth solution.
[0045] Nucleus solution (Seed Solution preparation steps The core solution preparation steps include a first core solution preparation step of providing a hexadecyltrimethylammonium bromide (CTAB) solution, a second core solution preparation step of adding a potassium bromide solution to the CTAB solution, a third core solution preparation step of adding a chloroauric (III) acid solution to the mixed solution obtained in the second core solution preparation step, a fourth core solution preparation step of mixing an aqueous sodium borohydride solution with the mixed solution obtained in the third core solution preparation step while stirring, and a fifth core solution preparation step of leaving the mixed solution obtained in the fourth core solution preparation step to stand under temperature conditions of 20 to 40°C for 30, 45, 60, 75, or 80 minutes within a range between any two of the numerical values exemplified here.
[0046] The core solution preparation step may include a core solution preparation standing step, following the fourth core solution preparation step, in which the mixed solution obtained in the fourth core solution preparation step is allowed to stand for 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 minutes, within a range between any two of the numerical values exemplified here.
[0047] In the nuclei solution preparation step, the concentration ratio of CTAB to potassium bromide is 1:0.05 to 0.15 (0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, and may be within a range between any two of the numerical values exemplified here). In the nucleus solution preparation step, the concentration ratio of CTAB to gold(III) chloride is 1:0.001 to 0.003 (0.0015, 0.0016, 0.0017, 0.0018, 0.0019, 0.0020, 0.0021, 0.0022, 0.0023, 0.0024, 0.0025, 0.0026, 0.0027, 0.0028, 0.0029, 0.0030, and may be within a range between any two of the numerical values exemplified here). In the nucleus solution preparation step, the concentration ratio of CTAB to sodium borohydride is 1:0.001 to 0.010 (0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, and may be within a range between any two of the numerical values exemplified here).
[0048] Primary Growth Solution Preparation Steps The first growth solution preparation step includes a first growth solution preparation step of providing a CTAB solution, a second growth solution preparation step of adding a potassium bromide solution to the CTAB solution, a third growth solution preparation step of adding a silver nitrate (I) solution to the mixed solution obtained in the second growth solution preparation step, a fourth growth solution preparation step of adding a chloroauric (III) acid solution to the mixed solution obtained in the third growth solution preparation step, a fifth growth solution preparation step of adding an L-ascorbic acid solution to the mixed solution obtained in the fourth growth solution preparation step, and a sixth growth solution preparation step of adding the mixed solution obtained in the fifth nucleus solution preparation step (nucleus solution) to the mixed solution obtained in the fifth first growth solution preparation step and stirring.
[0049] In the first growth solution preparation step, the concentration ratio of CTAB to potassium bromide is 1:0.05 to 0.15 (0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to silver nitrate (I) is 1:0.001 to 0.003 (0.0015, 0.0016, 0.0017, 0.0018, 0.0019, 0.0020, 0.0021, 0.0022, 0.0023, 0.0024, 0.0025, 0.0026, 0.0027, 0.0028, 0.0029, 0.0030, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to gold (III) chloride is 1:0.005-0.015 (0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to L-ascorbic acid is 1:0.005-0.015 (0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to gold in the nucleation solution was 1:0.5×10 -6 ~5.5×10 -6 (0.5×10 -6 , 1.5×10 -6 , 2.0×10 -6 , 2.5×10 -6 , 3.0×10 -6 , 3.5×10 -6 , 4.0×10 -6 , 4.5×10 -6 , 5.0×10 -6 , 5.5×10 -6 and may be in a range between any two of the numerical values given herein.
[0050] Secondary Growth Solution Preparation Step The second growth solution preparation step includes a first growth solution preparation step in which an L-ascorbic acid solution is added to the first growth solution at an inflow rate of 0.5 to 2.0 mL / h (0.50, 0.75, 1.00, 1.25, 1.50, 1.75, 2.00, 2.25, 2.50, 2.75, 3.00 mL / h, within the range between any two of the numerical values exemplified herein) while stirring the mixed solution (first growth solution) obtained in the sixth growth solution preparation step; a second growth solution preparation step in which the mixed solution obtained in the first growth solution preparation step is stirred for 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 minutes, within the range between any two of the numerical values exemplified herein; and a third growth solution preparation step in which the mixed solution obtained in the second growth solution preparation step is allowed to stand for a time period of 12, 18, 24, 30, or 36 hours, within the range between any two of the numerical values exemplified herein.
[0051] In the second growth solution preparation step, the concentration ratio of gold to ascorbic acid in the first growth solution is 1:0.1 to 1.0 (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, and may be within a range between any two of the numerical values exemplified here).
[0052] Coating step of gold nanorods with silica For example, when tetraethoxysilane (TEOS) is used as the alkoxysilane, the coating step of coating the gold nanorods with silica includes a first silica coating step of mixing, while stirring, an MeOH solution in which commercially available gold nanorods or gold nanorods obtained by the above-mentioned method for producing gold nanorods are dispersed, and an NaOH solution, and a second silica coating step of mixing, while stirring, the mixed solution obtained by the first silica coating step and an MeOH solution in which TEOS is dissolved. The concentration ratio of the gold nanorods to NaOH in the first silica coating step is 1:0.8 to 1.5 (0.8, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, and may be within a range between any two of the numerical values exemplified here). The concentration ratio of the gold nanorods to TEOS in the second silica coating step is 1:3 to 15 (3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, and may be within a range between any two of the numerical values exemplified here). The coating step of covering the gold nanorods with silica may include a heating and standing step following the second silica coating step, in which the mixed solution is left standing at a temperature of 20°C to 30°C for 12, 18, 24, 30, or 36 hours, and may be within a range between any two of the numerical values exemplified here.
[0053] In the second silica coating step, the MeOH solution in which TEOS is dissolved may be added to the MeOH solution in which gold nanorods are dispersed, in 2 to 4 portions every 20 to 40 minutes. In the first silica coating step, the MeOH solution in which gold nanorods are dispersed may be a 20, 22, 24, 26, 28, or 30% MeOH solution, and may be within a range between any two of the values exemplified here. The stirring time in the second silica coating step may be 10, 15, 20, 25, 30, 35, or 40 minutes, and may be within a range between any two of the values exemplified here.
[0054] In addition, the method for producing gold nanorods and the method for covering gold nanorods with silica may be the methods disclosed in JP 2018-127699 A. EXAMPLES
[0055] Experimental Example 1 Synthesis of Au nanorods (AuNR) The seed-mediated method was used to synthesize hexadecyltrimethylammonium bromide (CTAB)-protected AuNR. The synthesis scheme is shown in Figure 1.
[0056] The samples used are as follows: ·milliQ (Use a thermostatic bath at 30℃) Hexadecyltrimethylammonium bromide (CTAB) (Nacalai Tesque, MW= 364.45) [ka] Potassium bromide (KBr) (Kishida Chemical, MW= 119.0) ·Chloroauric acid tetrahydrate (HAuCl4) (Nacalai Tesque, MW= 411.85) Sodium borohydride (NaBH4) (Nacalai Tesque, MW= 37.83) Silver nitrate(I) (AgNO3) (Wako Chemicals, MW= 169.87) ·L-Ascorbic Acid (AA) (Nacalai Tesque, MW= 176.13)
[0057] The samples were prepared as follows. <Seed Solution> 0.125 M CTAB aq. The solution was prepared by dissolving CTAB (0.3645 g, 1.0 mmol) in milliQ (8.0 mL). 0.1 M KBr aq. This was prepared by dissolving KBr (120.5 mg, 1.0 mmol) in milliQ (10 mL). 2.4 mM HAuCl4aq. Prepared by diluting 4.6 mM HAuCl4aq. 10 mM NaBH4aq. NaBH4 (3.8 mg, 0.1 (mmol) in ice-cold milliQ (10 mL). <Primary Growth Solution> 0.122 M CTAB aq. The solution was prepared by dissolving CTAB (3.4314 g, 9.4 mmol) in milliQ (77 mL). 0.9412 M KBr aq. This was prepared by dissolving KBr (1.1203 g, 9.4 mmol) in milliQ (10 mL). 19.2 mM AgNO3aq. AgNO3(39.3 mg, 0.23 mmol) to milliQ (12.05 mL). 4.6 mM HAuCl4aq. HAuCl4·4H2O (255.49 mg, 0.62 mmol) was dissolved in milliQ (134.858 mL). 0.105 M AA aq. AA (186.5 mg, 1.1 mmol) was dissolved in milliQ (10 mL) to prepare the solution. <Secondary Growth Solution> 9.48 mM AA aq. AA (16.7 mg, 94.8 µmol) was dissolved in milliQ (10 mL). 1-1 Preparation of seed solution 14 In a mL glass sample bottle, add 0.125 M CTAB aq. (8.0 mL, 1.0 mmol), 0.1 M KBr aq. (1.0 mL, 0.1 mmol), and 2.4 mM HAuCl4 4H2O aq. (1.0 mL, 2.4 µmol) were added in that order. Then, the mixture was stirred vigorously at room temperature. 10 mM NaBH4aq. (0.6 mL, 6.0 µmol) was added and stirring was continued for 2 minutes. Then, stirring was stopped and the mixture was left to stand for 3 minutes. After mixing by inversion 7 times, the mixture was left to stand in a water bath at 30°C for 1 hour. The total volume of the nuclei solution was 10.6 mL, and the final concentrations were as follows: Final concentration [CTAB] = 94.34 mM [KBr] = 9.43 mM [HAuCl4 4H2O] = 0.226 mM [NaBH4] = 0.556 mM
[0058] 1-2 Preparation of Primary Growth Solution 250 0.122 M CTAB aq. (77 mL, 9.39 mmol) was placed in a 3 mL medium bottle and stirred at room temperature. 0.9412 M KBr aq. (1.0 mL, 0.9412 mmol), 19.2 (1.0 mL, 19.2 µmol) was added, and then 4.6 0.105 M AA aq. (1.0 mL, 0.105 mmol) was added in that order. 0.135 mL of the above nuclei solution (Au Seed) that had been left to stand for exactly one hour was added to this solution, and the mixture was stirred vigorously. The total volume of the first growth solution was 100.135 mL, and the final concentrations were as follows: Final concentration [CTAB] = 94.0 mM [KBr] = 9.40 mM [AgNO3] = 0.192 mM [HAuCl4 4H2O] = 0.919 mM [AA] = 1.05 mM [Au seed] = 0.305 µM
[0059] 1-3 Preparation of Secondary Growth Solution While the first growth solution was being vigorously stirred at room temperature, 9.48 mM AA aq. (5.00 mL, 47.4 µmol) was added. A microsyringe pump (AS ONE MSP-1D, syringe inner diameter: 17.0 mm, inflow volume: 5.00 mL, inflow rate: 1.75 mL / h, Thermo Syringe 10 mL ss-10Sz (plastic)) was used to introduce the aq. The stirring was continued for 10 min, after which the stirring was stopped. The entire volume (105.135 mL) was transferred to a 200 mL medium bottle and allowed to stand in an incubator at 25°C for 24 hours. The total volume of the second growth solution was 100.135 mL, and the final concentrations were as follows: [AA] = 0.451 mM [Au] = 0.88 mM
[0060] 1-4 AuNR purification After leaving it to stand for 24 hours, the AuNR (105.135 mL) was transferred to six 50 mL plastic centrifuge tubes at approximately 17.5 mL each. After that, centrifugation (10,000 rpm [9,840 × g], 30 min, 25°C) was performed, the supernatant was removed, and the solution was redispersed to the same size using milliQ. The solution thus prepared was designated AuNR / milliQ.
[0061] The absorption spectrum of the created AuNR was measured (PMMA cell, optical path length: 1 cm, [AuNR] = 0.0736 nM). The results are shown in Figure 2. As shown in Figure 2, the maximum absorption wavelength peak was shown at 786 nm. In addition, a field emission scanning electron microscope The AuNR was observed using a field emission scanning electron microscope (FE-SEM) (Figure 3), and the particle size distribution of the AuNR (n=200) was calculated from the FE-SEM image (Figure 4). The distribution results are shown in Table 1.
[0062] [Table 1]
[0063] 1-5 Discussion From the above results, it was confirmed by FE-SEM observation that AuNR was successfully synthesized. In addition, it was confirmed by absorption spectrum measurement that it has absorption in the near infrared region.
[0064] Experimental example 2 Silica coating of AuNR (AuNR@TEOS) Silica-coated AuNR (AuNR@TEOS) was prepared using tetraethoxysilane (TEOS). The preparation scheme is shown in Figure 5.
[0065] The samples used are as follows: ·AuNR / milliQ ([Au]= 0.88 mM, [AuNR]= 0.736 nM) Tetraethoxysilane (TEOS) (MW= 208.33) (0.934 g / mL) ·milliQ MeOH Sodium hydroxide (NaOH) (MW= 40.0)
[0066] The samples were prepared as follows. 0.1 M NaOH aq. NaOH (94.7 mg, 2.4 mmol) was dissolved in milliQ (23.7 mL). 20 vol% (0.89 M) TEOS / MeOH TEOS (100 µL, 0.45 mmol) and MeOH (400 µL).
[0067] 2-1 Preparation of AuNR@TEOS 15 AuNR / milliQ (5.0 mL) into a PP centrifuge tube and centrifuge (8,000 rpm [6,011 × g], After centrifugation, the supernatant was diluted with 1.25 1.25 mL of the solution was removed, and MeOH (1.25 mL) was added and redispersed. The resulting solution was AuNR / 25% MeOH aq. The total volume of the solution was 5.0 mL, and the final concentration was [Au] = 0.88 mM.
[0068] AuNR / The entire amount (5.0 mL) of 25% MeOH aq. was placed in a 30 mL wide-mouth PP bottle (film case) and stirred at room temperature. 0.1 M NaOH aq. (50 µL, 5.0 µmol) was added, and 20 vol% TEOS / MeOH (15 µL, 13.4 µmol) was added three times every 30 minutes, stirred for 30 minutes, and then left to stand in an incubator at 25°C for 24 hours. The total volume of the solution was 5.095 mL, and the final concentrations were as follows: Final concentration [Au] = 0.864 mM [NaOH] = 0.98 mM [TEOS] = 7.86 mM
[0069] After leaving it for 24 hours, the entire solution was (5.095 mL) Transfer to a 15 mL PP centrifuge tube and centrifuge. (8,000 rpm [6,011 × g], 30 min, 25°C). The supernatant was removed, and the mixture was redispersed in MeOH to the same volume. The mixture was centrifuged at rpm [3,381 × g], 30 min, 25°C, the supernatant was removed, and the mixture was filled up to 5.0 mL with MeOH. Then, the entire amount (5.0 mL) was transferred to a 14 mL glass sample bottle, and the solution was dissolved in AuNR@TEOS / The total volume of the solution was 5.0 mL, and the final concentration was [Au] = It is 0.88 mM.
[0070] The absorption spectrum, Zeta potential, and Fourier transform infrared spectroscopy (FT-IR) of AuNR and AuNR@TEOS were measured (Figures 6, 7, and 8, respectively). In addition, AuNR@TEOS was observed using FE-SEM (Figure 9), and the silica layer distribution (n=200) of AuNR@TEOS was calculated from the FE-SEM image (Figure 10). The distribution results are shown in Table 2.
[0071] [Table 2]
[0072] According to Figure 10, it can be seen that the silica layer of AuNR@TEOS has a thickness of at least 15 nm.
[0073] 2-2 Discussion FE-SEM observation revealed that the AuNR surface was coated with silica. Therefore, absorption spectrum measurement showed a shift in the maximum absorption wavelength due to a change in the local refractive index of the particle surface. In addition, in the Zeta potential measurement, it is believed that by coating silica onto the positively charged CTAB-protected AuNR surface, negatively charged hydroxyl groups derived from silica are introduced onto the particle surface, shifting the Zeta potential to a negative value. In the FT-IR measurement, a value of 1100 was observed, which was not observed in the CTAB-protected AuNR. cm -1 It was confirmed that new peaks originating from the surrounding Si-O bonds appeared. The above results revealed that AuNR@TEOS (silica coating) was produced.
[0074] Comparative Experimental Example A: Introduction of 3-aminopropyltriethoxysilane into AuNR AuNR@APTES was prepared by introducing 3-aminopropyltriethoxysilane (APTES) into AuNR.
[0075] The samples used are as follows: ·AuNR / milliQ ([Au]= 0.88 mM, [AuNR]= 0.736 nM) ·3-Aminopropyltriethoxysilane (APTES) (MW= 221.37) (0.946 g / mL) ·milliQ MeOH Sodium hydroxide (NaOH) (MW= 40.0)
[0076] The samples were prepared as follows. 0.1 M NaOH aq. NaOH (94.7 mg, 2.4 mmol) was dissolved in milliQ (23.7 mL). ·10 vol% (0.427 M) APTES / MeOH APTES (50 µL, 0.21 mmol) and MeOH (450 µL).
[0077] A-1 Preparation of AuNR@ APTES 15 AuNR / milliQ (5.0 mL) into a PP centrifuge tube and centrifuge (8,000 rpm [6,011 × g], After centrifugation, the supernatant was diluted with 1.25 1.25 mL of the solution was removed, and MeOH (1.25 mL) was added and redispersed. The resulting solution was AuNR / 25% MeOH aq. The total volume of the solution was 5.0 mL, and the final concentration was [Au] = 0.88 mM.
[0078] AuNR / The entire amount (5.0 mL) of 25% MeOH aq. was placed in a 30 mL wide-mouth PP bottle (film case) and stirred at room temperature. 0.1 M NaOH aq. (50 µL, 5.0 µmol) was added, and the mixture was stirred for 10 vol% (0.427 M) APTES / MeOH (15 µL, 6.40 µmol) was added twice every 30 minutes, stirred for 30 minutes, and then 10 vol% (0.427 M) APTES / MeOH (20 µL, 8.54 µmol) was added and stirred for 30 min. Then, the mixture was allowed to stand for 24 hours in an incubator at 25° C. The total amount of the solution was 5.1 mL, and the final concentrations were as follows: Final concentration [Au] = 0.863 mM [NaOH] = 0.98 mM [APTES] = 4.19 mM
[0079] After leaving it for 24 hours, the entire solution (5.1 mL) was transferred to a 15 mL PP centrifuge tube and centrifuged (8,000 rpm [6,011 × g], 30 min, 25°C). The supernatant was removed and the mixture was redispersed in MeOH to an equal volume. Centrifuge again (6,000 rpm [3,381 × g], 30 min, The supernatant was removed and the solution was filled up to 5.0 mL with MeOH. After that, the entire amount (5.0 mL) was transferred to a 14 mL glass sample bottle, and the prepared solution was named AuNR@APTES / MeOH. The total volume of the solution was 5.0 mL, and the final concentration was [Au] = 0.88 mM.
[0080] Absorption spectra of AuNR, AuNR@TEOS, and AuNR@APTES (glass cell, optical path length 1 mm, [AuNR] = 0.736 nM) was measured (Figure 11). In addition, AuNR@APTES was observed using FE-SEM (Figure 12).
[0081] A-2 Discussion As shown in Figure 11, the absorption spectrum of AuNR@APTES showed a clear decrease in the absorption band due to the inability to disperse the sample. In addition, the FE-SEM image in Figure 12 also revealed that silica coating was not performed.
[0082] Experimental Example 3: Synthesis of 3-aminopropyltriethoxysilane-introduced AuNR@TEOS (AuNR@TEOS-APTES) APTES was used to detect 3-aminopropyltriethoxysilane (APTES). We prepared AuNR@TEOS (AuNR@TEOS-APTES) with (-NH2 group) introduced. The preparation scheme is shown in Figure 13.
[0083] The samples used are as follows: ·AuNR@TEOS / MeOH ([Au]= 0.88 mM, [AuNR]= 0.736 nM) Tetraethoxysilane (TEOS) (MW= 208.33) (0.934 g / mL) ·3-Aminopropyltriethoxysilane (APTES) (MW= 221.37) (0.946 g / mL) ·milliQ MeOH Sodium hydroxide (NaOH) (MW= 40.0)
[0084] The samples were prepared as follows. 0.1 M NaOH aq. NaOH (94.7 mg, 2.4 mmol) was dissolved in milliQ (23.7 mL). 20 vol% (0.89 M) TEOS / MeOH The solution was prepared by mixing TEOS (100 µL, 0.45 mmol) and MeOH (400 µL). 10 vol% (0.427 M) APTES / MeOH APTES (50 µL, 0.21 mmol) and MeOH (450 µL).
[0085] 3-1 Preparation of AuNR@TEOS-APTES 15 AuNR@TEOS / MeOH (5.0 mL) was added to a PP centrifuge tube. mL) and centrifuge (8,000 rpm [6,011 × g], The solution was then redispersed by adding 3.75 mL of milliQ. The solution was then redispersed in AuNR@TEOS / 25% MeOH. The total volume of the solution was 5.0 mL, and the final concentration was [Au] = It is 0.88 mM.
[0086] AuNR@TEOS / The entire amount (5.0 mL) of 25% MeOH aq. was placed in a 30 mL wide-mouth PP bottle (film case) and stirred at room temperature. 0.1 M NaOH aq. (50 µL, 5.0 µmol) was added, and then 10 Vol% (0.427 M) APTES / MeOH (50 µL, 21.4 µmol) was added and stirring was continued for 5 min. Next, stirring was started in a water bath at 50° C., and stirring was continued for 5 hours. The total volume of the solution was 5.1 mL and the final concentrations were as follows: Final concentration [Au] = 0.863 mM [NaOH] = 0.98 mM [APTES] = 4.19 mM
[0087] After stirring for 5 hours, the entire solution was The mixture (5.1 mL) was transferred to a 15 mL polypropylene centrifuge tube and centrifuged (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the mixture was redispersed in MeOH to an equal volume. Centrifuge again (6,000 rpm [3,381 × g], 30 min, The supernatant was removed and the solution was filled up to 5.0 mL with MeOH. Then, the entire solution (5.0 mL) was transferred to a 10 mL glass sample bottle to give AuNR@TEOS-APTES / MeOH. The total volume of the solution was 5.0 mL and the final concentrations were as follows: Final concentration [Au] = 0.88 mM (theoretical value) [-NH2] = 4.27 mM (theoretical value)
[0088] The absorption spectrum, Zeta potential, and FT-IR of AuNR, AuNR@TEOS, and AuNR@TEOS-APTES were measured (Figures 14, 15, and 16, respectively). In addition, AuNR@TEOS-APTES was observed using FE-SEM (Figure 17), and the silica layer distribution (n=200) of AuNR@TEOS-APTES was calculated from the FE-SEM image (Figure 18). The distribution results are shown in Table 3.
[0089] [Table 3]
[0090] According to Figure 18, it can be seen that the silica layer of AuNR@TEOS-APTES has a thickness of at least 15 nm.
[0091] 3-2 Discussion Absorption spectrum measurement revealed a shift in the maximum absorption wavelength. This is thought to be due to a change in the local refractive index caused by the addition of new amino groups to the particle surface. Furthermore, when we looked at the Zeta potential, we confirmed that the particle surface was negatively charged due to the hydroxyl groups derived from the silica coating, but the surface charge shifted to positive by the addition of new amino groups. For these reasons, it is suggested that amino groups have been introduced. Furthermore, FE-SEM observation showed no change in particle size.
[0092] Experimental Example 4: Modification of AuNR@TEOS-APTES with Dansyl Groups Dansyl chloride was used to prepare AuNR@TEOS-APTES modified with a Dansyl group (AuNR@TEOS-APTES-Dansyl). The preparation scheme is shown in Figure 19.
[0093] The samples used are as follows: ·AuNR@TEOS-APTES / MeOH ([Au] = 0.88 mM, [AuNR] = 0.736 nM, [-NH2] = 4.27 mM (theoretical value)) Dansyl Chloride (MW= 269.75) CH2Cl2 MeOH Triethylamine
[0094] The samples were prepared as follows. Dry CH2Cl2 Add CH2Cl2 to a 200 mL eggplant flask. (100 mL) and an appropriate amount of CaCl2 were added, and the flask was sealed with a glass stopper. The flask was then shaken well and allowed to stand at room temperature overnight. After standing, it was distilled under a nitrogen atmosphere to obtain dry CH2Cl2. The obtained dry CH2Cl2 was transferred to an eggplant flask and covered with a septum to prevent it from coming into contact with air. 2.38 mM Dansyl Chloride / Dry CH2Cl2 Dansyl Chloride (5.76 mg, 21.4 µmol) in Dry CH2Cl2 (9.0 mL).
[0095] 1.5 Put AuNR@TEOS-APTES / MeOH (1.0 mL) into a mL Eppendorf tube and centrifuge (8,000 rpm [5,796 × g], 30 min, 25℃), the supernatant was removed, and the mixture was redispersed in dry CHCl to an equal volume. Triethylamine (3.0 µL, 21.4 µmol) was added to the prepared AuNR@TEOS-ATPES / dry CHCl, and the entire volume was poured into a 100 mL two-necked eggplant flask. (about 1.0 mL) was transferred and stirred under a nitrogen atmosphere. (9.0 mL) was added and heating to reflux was started. After 8 hours, stirring and heating to reflux were stopped. The total volume of the solution is 10 mL and the final concentrations are as follows: Final concentration [Au] = 0.088 mM [-NH2] = 0.427 mM [Dansyl Chloride] = 2.14 mM [Triethylamine] = 2.14 mM
[0096] The prepared solution was transferred to two 15 mL PP centrifuge tubes (5.0 mL each) and centrifuged (8,000 The pellet was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the pellet was redispersed to equal size in CHCl2. The pellet was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the pellet was redispersed to equal size in CHCl2. The pellet was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the pellet was redispersed to equal size in CHCl2. The pellet was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the pellet was redispersed to equal size in MeOH. The pellet was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the pellet was redispersed to equal size in MeOH. Centrifuge again (8,000 rpm [6,011 × g], 30 min, The solution was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the solution was redispersed in MeOH to an equal volume. The solution was centrifuged again (8,000 rpm [6,011 × g], 30 min, 25°C), the supernatant was removed, and the solution was redispersed in MeOH to an equal volume. The total volume of the solution was 10 mL, and the final concentrations were as follows: Final concentration [Au] = 0.088 mM [-NH-Dansyl] = 0.427 mM
[0097] AuNR@TEOS-APTES, AuNR@TEOS-APTES-Dansyl, and Dansylated Hexylamine hexylamine) (Figures 20 and 21), the spectrum showing the difference in absorption spectrum between AuNR@TEOS-APTES and AuNR@TEOS-APTES-Dansyl (i.e., the difference before and after Dansyl group modification) (Figure 22), FT-IR (Figure 23) and Zeta potential (Figure 24) of AuNR, AuNR@TEOS, AuNR@TEOS-APTES and AuNR@TEOS-APTES-Dansyl were measured. In addition, AuNR@TEOS-APTES-Dansyl was observed using FE-SEM (Figure 25), and the silica layer distribution (n=200) of AuNR@TEOS-APTES-Dansyl was calculated from the FE-SEM image (Figure 26). The distribution results are shown in Table 4.
[0098] [Table 4]
[0099] According to Figure 18, it can be seen that the silica layer of AuNR@TEOS-APTES-Dansyl has a thickness of at least 15 nm.
[0100] 4-2 Discussion Absorption spectrum measurements confirmed new peaks at around 220 nm, 250 nm, and 330 nm derived from Dansyl groups. FT-IR measurements showed that the peak intensity derived from C-H bonds was greater than that derived from Si-O bonds. This is thought to be because the CH bonds of the Dansyl groups were strongly reflected in the IR spectrum due to the modification with Dansyl groups. In the Zeta potential measurement, the positive charge on the particle surface due to the amino groups was weakened by the bonding of the Dansyl groups with the amino groups, and a shift in the Zeta potential in the negative direction was observed. From the above, it was found that the particle surface was successfully modified with Dansyl groups. Furthermore, no change in particle size was observed by FE-SEM observation.
[0101] Experimental Example 5 Number of Dansyl groups modified per AuNR@TEOS-APTES-Dansyl particle Curve fitting was performed using the nonlinear least squares method, and the number of Dansyl groups modified per AuNR@TEOS-APTES-Dansyl particle was calculated by estimating the fitting parameters that best fit the data. In order to reduce the influence of the peak derived from the long axis of AuNR@TEOS-APTES-Dansyl, curve fitting was performed in the wavelength range of 210-450 nm. As a result, the calculated AuNR@TEOS-APTES-Dansyl The number of Dansyl groups introduced per particle is (3.68±0.77)×10 4 There were 100 pieces.
[0102] Experimental Example 6 Fluorescence of AuNR@TEOS-APTES-Dansyl Fluorescence spectrum measurement of AuNR, AuNR@TEOS, AuNR@TEOS-APTES, and AuNR@TEOS-APTES-Dansyl (quartz cell, optical path length 1 cm, Ex:335 The fluorescence spectrum was measured (nm) (Figure 27). As a result, the fluorescence after modification with Dansyl groups was confirmed by fluorescence spectrum measurement.
[0103] Furthermore, AuNR, AuNR@TEOS, AuNR@TEOS-APTES, and AuNR@TEOS-APTES-Dansyl were each placed in a vial and irradiated with UV (365 Fluorescence was observed by irradiating the sample with light (nm) (Figure 28). Fluorescence was confirmed only in AuNR@TEOS-APTES-Dansyl.
[0104] Experimental Example 7 Fluorescence spectrum measurement and fluorescence quantum yield calculation of AuNR@TEOS-APTES-Dansyl The fluorescence quantum yield of AuNR@TEOS-APTES-Dansyl was calculated by the relative method (Figures 29, 30, and 31). The fluorescence quantum yield was calculated using the integrated area of the measured fluorescence spectrum and the absorbance of the absorption spectrum (Ex: 335 nm). The fluorescence quantum yield was calculated three times in total to calculate the average value and standard deviation of the fluorescence quantum yield. The formula for calculating the fluorescence quantum yield by the relative method is shown below.
number
[0105] The values measured by the absorption spectrum measurement and the fluorescence spectrum measurement shown in Tables 5 to 7 were substituted into formula (1). (Standard material: Quinine Sulfate dihydrate, unknown sample: AuNR@TEOS-APTES-Dansyl (the difference spectrum with AuNR@TEOS-APTES is used for the absorbance at the excitation wavelength), Ex: 335.0 nm), relative quantum yield Φ of AuNR@TEOS-APTES-Dansyl F was calculated.
[0106] [Table 5]
[0107] [Table 6]
[0108] [Table 7]
[0109] From the above three calculations of the fluorescence quantum yield, the fluorescence quantum yield of AuNR@TEOS-APTES-Dansyl is Φ F =8.23±0.67%. From this result, it can be said that AuNR@TEOS-APTES-Dansyl has fluorescence. Furthermore, when the fluorescence spectrum measurements of AuNR, AuNR@TEOS, and AuNR@TEOS-APTES were performed as control measurements, no fluorescence was confirmed (see Figure 27). From the above, it is believed that the fluorescence of AuNR@TEOS-APTES-Dansyl is derived from the Dansyl group. These results indicate that the particle surface was successfully modified with Dansyl groups. Furthermore, the fluorescence of AuNR@TEOS-APTES-Dansyl could be confirmed.
[0110] As described above, the present invention makes it possible to avoid quenching caused by light energy transfer near the gold nanorod interface by making the silica layer 15 nm thick or more, thereby realizing a stable and highly sensitive luminescent agent. Furthermore, in the above examples, since quenching is avoided despite a wide range of thickness distribution of the silica layer, the conditions for the thickness of the silica layer during production are not strict, production is easy, and production costs can be reduced.
[0111] The silica-coated gold nanorods bound to the labeling substance of the present invention can be used as, for example, contrast agents, nanotherapeutic drugs, bioimaging agents, labeling agents, etc. In this case, since both the emission of Dansyl, a fluorescent agent, and the diffraction of light by the gold rods can be used, it is useful as a bioimaging agent because it allows observation with both a fluorescent microscope and an electron microscope. For example, when administered to cells in vitro, it is possible to confirm which cells have taken up the gold nanorods of the present invention with a fluorescent microscope, and then fine observation can be made with an electron microscope. Similarly, when administered to experimental animals, it is possible to confirm which organs have taken up the gold nanorods with a fluorescent microscope, and then fine observation can be made with an electron microscope.
[0112] As for the application of nano-therapeutic drugs in the human body, the present invention is harmless to the human body because it uses gold nanorods. First, silica-coated gold nanorods bound to the labeling substance of the present invention are delivered to the pathological site of cancer or the like by a drug delivery system or the like. The gold nanorods are heated by irradiating near-infrared light to target the fluorescent light, and treatment can be performed.
[0113] In addition, the present invention is useful for contrast agents, labeling agents, and the like that emit fluorescence. [Industrial Applicability]
[0114] The silica-coated gold nanorods of the present invention bound to a labeling substance can be used, for example, as contrast agents, nanotherapeutic agents, bioimaging agents, labeling agents, and the like.
Claims
1. Gold nanorods, a silica layer covering the gold nanorods; a spacer bonded to the silica layer; a dansyl group attached to the spacer by a chemical bond; 1. A labeled silica coated gold nanorod comprising:
2. 2. The labeled silica-coated gold nanorod of claim 1, wherein the thickness of the silica layer is 15 nm or more.
3. The spacer is derived from a silane coupling agent having a Si atom and four functional groups directly or indirectly connected to the Si atom, The four functional groups include at least one inorganic functional group and at least one organic functional group.
3. The labeled silica-coated gold nanorod according to claim 1 or 2.
4. 4. The labeled silica-coated gold nanorod according to claim 3, wherein the organic functional group is at least one selected from the group consisting of a vinyl group, an epoxy group, a styryl group, a methacryloyl group, an acryloyl group, an amino group, a ureido group, an isocyanate group, an isocyanurate group, and a mercapto group.
5. An introduction step of introducing a spacer into the silica layer of the silica-coated gold nanorod; a bonding step of bonding a dansyl group to the spacer by chemical bonding; The method for producing labeled silica-coated gold nanorods comprising the steps of:
6. The method for producing labeled silica-coated gold nanorods according to claim 5 , wherein the thickness of the silica layer is 15 nm or more.
Citation Information
Patent Citations
Gold nanoflower structure and gold nanoflower / quantum dot composite probe for living cell immunofluorescent labeling and photothermal therapy
EP3037195A1
Embedded fine particles, method for preparing the same and use
JP2009149593A
High-sensitivity immunological assay using coated nanoparticles
JP2011516889A
Fluorescent nanoparticle, phosphor substrate, light-emitting device and display device
JP2016216547A
Method for synthesizing highly-dispersible silica-coated gold nanorod and dispersion liquid of synthesized gold nanorod
JP2018127699A